(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The connection between language and gender is significant, especially within the realm of education. In India, female students hailing from regional language backgrounds encounter distinct obstacles in higher education, particularly in relation to their command of English. In Indian higher education institutions, a notable distinction exists between female and male students, with the former predominantly hailing from regional mediums. This article emphasises the constraints imposed by language barriers on engagements with English-speaking peers and educators, resulting in a sense of inadequacy. It emphasises the importance of scholarship programs that provide English courses and mentorship, as well as language support initiatives such as tutoring and language exchanges. The article highlights the significance of English proficiency in shaping career trajectories, revealing that individuals fluent in English tend to have enhanced employability within multinational corporations and technology sectors. English serves as a medium for connection while enhancing self-assurance and professionalism, essential for success in competitive employment landscapes. The research advocates for a holistic approach, incorporating workshops, mentorship, and modifications to the curriculum, aimed at tackling disparities in education and fostering inclusive, nurturing learning spaces.